(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Stevanus, Pharmawati M. 2021. Biodiversity and phylogenetic analyses using DNA barcoding rbcL gene of seagrass from Sekotong, West Lombok, Indonesia. Biodiversitas 22: 50-57. West Lombok, Indonesia is one of the locations that is thought to have a quite high diversity of seagrass. Information on the diversity of seagrass species is important due to the important value of seagrass in the marine ecosystem. This research aimed to analyze biodiversity and phylogenetic of seagrass from Sekotong, West Lombok, Indonesia using DNA barcoding of rbcL gene. As many as 35 samples from seven morphologically identified species (Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halodule pinifolia, Halophila ovalis, and H. minor) were taken from four Gilis (small island) in Sekotong. The DNA was amplified for the rbcL gene and sequence analyses using BLAST were conducted to determine the species. Phylogenetic analyses were carried out using three evolutionary algorithms using Neighbor-Joining, Maximum Likelihood and Bayesian analysis with 1000 bootstrap. The rbcL gene was successfully amplified from all samples with a maximum length of 552 bp. The phylogenetic analysis showed that clades were split by family and genera where six clades were formed (Enhalus acoroides, T. hemprichii, Halophila complex, H. pinifolia, S. isoetifolium, and C. rotundata) with more than 95% of bootstrap values for Neighbor-Joining and Bayesian. The p-distance values between species were 0.008-0.097 and the polymorphic site was not found within species. The rbcL sequences only confirmed five seagrass species out of seven morphologically identified species and the sequences generated from this study cannot discriminate Halophila ovalis and H. minor.